Rififi am Karfreitag - Mackenzie, John; Meheux, Phil; Hoskins, Bob; Mirren, Helen; Constantine, Eddie (Spirit Media GmbH, 2012)
Harold Shand (Hoskins) is an East End gangster on the up. An entrepreneurial thug with a beautiful wife (Mirren), Shand dreams of renovating London's Docklands, turning it into Europe's capital and the venue of choice for the 1988 Olympics. In a hands-across-the-water exercise he convinces a powerful American mafia boss (Constantine) to come to London to have a look at the operation and perhaps invest the necessary readies to turn the dream to reality ... Sharply scripted by Barry Keeffe, MacKenzie's film has a gritty realism which still exerts a powerful force. The film is also strangely portentous in light of the emergence of the Docklands area as an important source of business and commerce ... In his breakthrough role, Hoskins is a seething ball of ambition and aggression; part strutting Napoleon, part Reggie Kray, while Mirren and Constantine offer customary sterling support. A touchstone for many of the sub-standard gangster films Britain mercilessly churns out today, "The Long Good Friday" is classy fare and superior viewing to its modern counterparts in every way. [www.bbc.co.uk]
Keywords: Blu-Ray-Disc